Kontribusi dan Strategi Komite Sekolah sebagai Pilar Pengembangan Mutu Pendidikan - M, Rahmawati; Arfin, Arfin; Ahmad, Muhammad (Journal of Leadership, Management and Policy in Education, 2024)
This study aims to analyze the contributions and strategies of the school committee in supporting educational development at SMPN 11 Buteng. Using a qualitative descriptive approach, the study involved the principal, the school committee chairperson and secretary, teachers, and parents as subjects. Data were collected through observation, interviews, and documentation, with validity ensured through source, technique, and time triangulation. The results of the study indicate that the school committee plays a significant role as an Advisory Agency, Supporting Agency, Controlling Agency, and Mediator (Executive) in improving the quality of education. These roles include providing strategic input, supporting resources, monitoring accountability, and bridging communication between the school and the community. Thus, the contributions of the school committee at SMPN 11 Buteng serve as an important model for sustainable educational development.